The - Hull, Dennis (ECW Press, 1998)
Hockey legend Gordie Howe once said there were two superstars in the Hull family: Bobby, the Golden Jet and one of the greatest players ever to tie up a pair of skates, and his brother Dennis, who had a solid career with the Chicago Blackhawks. Dennis Hull outlines his life in hockey with humorous anecdotes, insights, and stories. Not just another sports autobiography, this book provides insight into the life of a hockey star without taking itself too seriously